Retraction Note: A Spiritual Prescription to Bereaved Parents of Children Died Due to Coronavirus Disease 2019 - Çaksen, Hüseyin (Journal of Child Science, 2022)
An investigation by the publisher found a number of articles, including this one, published in Journal of Child Science in Volume 12, Number 01, e117–e118, on September 29, 2022 (DOI: 10.1055/s-0042-1757146), with a number of concerns, including but not limited to undeclared conflicts of interest and manipulated peer review procedures. As a result, the publisher has retracted and removed this article.